Graphene-based nano-silicon composite aerogel negative electrode material and preparation method and application thereof
By coating nanosilicon particles in graphene aerogel to form a porous three-dimensional network structure, the problem of material rupture caused by changes in nanosilicon volume in sodium ion batteries is solved, the cycle stability and capacity of the battery are improved, and efficient Sodium ion transport and conductivity.
Patent Information
- Application Number
- CN202411445728.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-13
AI Technical Summary
The negative electrode material of existing sodium ion batteries is hard carbon material, due to structural instability and mechanical deformation, and the initial Coulomb efficiency is insufficient, and the nano-silicon changes in volume during charging and discharging, resulting in the material rupture and powderization, affecting the battery capacity and stability.
Graphene-based nano-silicon composite aerogel is used as the negative electrode material. By uniformly coating nano-silicon particles in graphene aerogel, a porous three-dimensional network structure is formed to alleviate the volume expansion problem and improve the conductivity and sodium ions transport capability. .
It significantly improves the cycle stability and capacity of sodium ion batteries, reduces battery manufacturing costs, and enhances conductivity and electrochemical properties.
Smart Images

Figure CN119133414A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, and in particular to a graphene-based nano-silicon composite aerogel negative electrode material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries are considered a potential energy storage technology due to their abundant resources, relatively low preparation costs, and environmental friendliness.
[0003] The negative electrode material is one of the key factors affecting the performance of sodium-ion batteries. In the current prior art, the negative electrode material of sodium-ion batteries is mainly hard carbon materials, which have good electrical conductivity. However, the pores and defects in the hard carbon materials can trigger electrochemical reactions, which will lead to the loss of some capacity. In addition, the structural instability and mechanical deformation in the hard carbon materials will also lead to the problem of insufficient initial coulombic efficiency in the first cycle. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a graphene-based nano-silicon composite aerogel negative electrode material and a preparation method and application thereof.
[0005] The present invention provides a graphene-based nano-silicon composite aerogel negative electrode material, which is used for a sodium ion battery. The raw materials for preparing the graphene-based nano-silicon composite aerogel negative electrode material include, by mass percentage:
[0006] Graphene / nano-silicon composite aerogel 75% to 85%, conductive agent 8% to 12% and binder 8% to 12%, totaling 100%.
[0007] It should be emphasized that the present invention takes into account that nano-silicon has an ultra-high theoretical lithium storage capacity, a high lithium insertion potential and a low cost, so the present invention uses nano-silicon as the matrix of the active material of the negative electrode material of the sodium ion battery, so as to improve the performance of the sodium ion battery by introducing nano-silicon. However, nano-silicon is currently mainly used in lithium-ion batteries as a negative electrode material for lithium-ion batteries. In the process of exploration, the present invention found that when pure silicon material is used as the active component of the negative electrode material of the sodium ion battery, since the volume change rate of silicon during the charging and discharging process is as high as 300% to 400%, this huge volume change will cause the silicon material to break and pulverize during the cycle, and lose electrical contact with the electrode, thereby causing serious capacity decay, resulting in the actual capacity of silicon used in sodium ion batteries being very low, and sodium cannot be effectively stored, which in turn makes it difficult to use silicon material as a negative electrode material for sodium ion batteries.
[0008] In order to limit or avoid the volume expansion of pure silicon materials during the charge and discharge process and improve the capacity of silicon as a negative electrode material for sodium ion batteries, the present invention attempts to introduce graphene on the basis of nano-silicon. Graphene can improve electron transfer and Na+ due to its high electronic conductivity, excellent mechanical strength and flexibility. + However, the present invention has found in the process of exploration that if graphene and nano-silicon are directly composited, although the electrochemical performance of nano-silicon can be improved to a certain extent, nano-silicon still has a tendency to aggregate, resulting in poor performance stability of the composite material of graphene and nano-silicon, which will inevitably decline during the charge and discharge process.
[0009] In order to improve the performance stability of the composite material, the present invention proposes to composite graphene with nano-silicon in the form of a graphene aerogel with a three-dimensional structure, and to use the graphene aerogel with a three-dimensional structure as a matrix, and to obtain a composite aerogel structure with a three-dimensional structure by uniformly coating and introducing nano-silicon particles inside the graphene aerogel, that is, to obtain the graphene / nano-silicon composite aerogel of the present invention. The porous three-dimensional network structure of the graphene aerogel in the graphene / nano-silicon composite aerogel can adapt to the volume expansion changes of the modified nano-silicon particles during the electrochemical reaction process, thereby effectively alleviating the volume expansion problem of silicon during the charge and discharge process and improving the cycle stability; moreover, the porous three-dimensional network structure of the graphene aerogel in the graphene / nano-silicon composite aerogel has a porous and high specific surface area structure, which can distribute nano-silicon in the graphene aerogel, effectively avoid the aggregation of nano-silicon, reduce the resistance during the transfer of sodium ions, greatly improve the transmission capacity of sodium ions, and improve the rate capacity of sodium ion batteries, thereby further improving the electrochemical performance of nano-silicon for sodium ion storage. Furthermore, the continuously interconnected graphene network provides favorable electron pathways against the cycling process, thereby improving the conductivity of the overall composite.
[0010] Based on the above, the present invention proposes to use graphene / nano silicon composite aerogel as the active material of the negative electrode material of the sodium ion battery, and to form a graphene / nano silicon composite aerogel negative electrode material by compounding the graphene / nano silicon composite aerogel, a conductive agent and a binder, so as to be used as the negative electrode material of the sodium ion battery, which greatly reduces the manufacturing cost of the battery compared to the preparation of lithium sodium ion batteries. Moreover, compared with the pure silicon negative electrode, the cycle stability and capacity of the graphene / nano silicon composite aerogel negative electrode material of the present invention are significantly improved.
[0011] In order to ensure that graphene and nano-silicon can form the above-mentioned graphene / nano-silicon composite aerogel with a three-dimensional aerogel structure, in some preferred embodiments of the present invention, the graphene / nano-silicon composite aerogel is prepared by the following steps:
[0012] S1, modifying nano silicon particles by using a modifier in an aqueous solution to obtain modified nano silicon particles.
[0013] S2, uniformly dispersing graphene oxide in water to form a graphene oxide suspension; sequentially dispersing the modified nano-silicon particles and the reducing agent in the graphene oxide suspension and mixing them to obtain a mixed solution.
[0014] S3, subjecting the mixed solution to a hydrothermal reaction, washing and freeze-drying to obtain a hydrogel precursor.
[0015] S4, heat-treating the hydrogel precursor in an inert atmosphere to obtain the graphene / nano-silicon composite aerogel.
[0016] It should be noted that the present invention has been found in the process of exploration that although both nano silicon and graphene have high surface energy, the bonding force may be poor due to electrostatic repulsion during direct compounding. Functional groups such as carboxyl and hydroxyl groups on the surface of graphene oxide can form stronger interactions with nano silicon, thereby improving the stability of the composite material. Moreover, the dispersibility of graphene oxide in aqueous solution is good, which helps to achieve uniform mixing of nano silicon and graphene oxide during the compounding process. Therefore, graphene oxide is used as a precursor raw material for forming graphene, by first compounding graphene oxide with nano silicon, and then removing the oxygen-containing functional groups on the surface of graphene oxide through a subsequent reduction process, thereby reducing graphene oxide to graphene, restoring the inherent properties of graphene, thereby achieving the compounding of graphene and nano silicon.
[0017] In the above S1, the present invention first modifies the nano silicon particles in an aqueous solution by a modifier to introduce positive charges on the surface of the nano silicon particles, thereby obtaining modified nano silicon particles with a large amount of positive charges on the surface, which is beneficial to the subsequent modification of the nano silicon particles and graphene oxide through electrostatic action. In some preferred embodiments of the present invention, the modifier used is any one of polydiallyldimethylammonium chloride, polyacrylamide and polyaniline. In some more preferred embodiments of the present invention, the modifier used is polydiallyldimethylammonium chloride, and polydiallyldimethylammonium chloride has better battery performance after nano silicon modification than other modifiers. In the present invention, polydiallyldimethylammonium chloride is hereinafter referred to as PDDA.
[0018] In some preferred embodiments of the present invention, when the nano-silicon particles are modified by using a modifier, the modifier is first dispersed in water, and then the nano-silicon particles are added, followed by ultrasonic treatment and stirring treatment in sequence, so that the modifier is fully in contact with the nano-silicon particles, and the surface of the nano-silicon is modified by electrostatic interaction and charge transfer, and positive charges are introduced on the surface of the nano-silicon. For example, taking PDDA as an example, during the process of full contact between PDDA and nano-silicon particles, electrostatic interactions occur between the cationic part of the PDDA molecule and the negative charges and active sites on the surface of the nano-silicon, which is the main driving force of the adsorption process. Through the adsorption and charge transfer of PDDA, the surface of the nano-silicon is modified, so that it has specific positive charge properties, thereby introducing positive charges on the surface of the nano-silicon.
[0019] In some more preferred embodiments of the present invention, the ultrasonic power of the ultrasonic treatment is 240 W, and the ultrasonic time is 1 h to 3 h. In some more preferred embodiments of the present invention, the stirring time of the stirring treatment is 6 h to 18 h.
[0020] In some preferred embodiments of the present invention, the mass ratio of the water to the nano-silicon particles is 50mL-100mL:120mg, to ensure that the amount of water used can achieve sufficient dispersion of the nano-silicon particles and the modifier, so that the modifier can fully modify the nano-silicon particles.
[0021] In some preferred embodiments of the present invention, the present invention takes into account that when preparing modified nano silicon particles, the amount of modifier added is excessive relative to the nano silicon particles. In order to obtain pure modified nano silicon particles, the product obtained after the modification treatment is subjected to multiple centrifugal washing treatments using water as a washing liquid to wash away the excess modifier, and then subjected to vacuum drying treatment to remove the influence of the solvent. The product of the vacuum drying treatment is the modified nano silicon particles. Among them, in some more preferred embodiments of the present invention, the centrifugal speed during each centrifugal washing treatment is 8000rpm to 10000rpm, and the time is 5min to 10min. In some more preferred embodiments of the present invention, the temperature of the vacuum drying treatment is 100℃ to 120℃, and the time is 24h to 36h.
[0022] In some preferred embodiments of the present invention, the mass ratio of the modifier to the nano-silicon particles is 20-30:1, so that the added modifier can fully modify the nano-silicon particles to uniformly introduce positive charges on the surface of the nano-silicon.
[0023] It should also be noted that the graphene oxide used in the present invention is prepared from natural graphite by a modified Hummers method. In some preferred embodiments of the present invention, the graphene oxide used is specifically prepared by the following steps:
[0024] 1) In an ice bath, slowly adding sodium nitrate to concentrated sulfuric acid to obtain a sulfuric acid solution of sodium nitrate; wherein the amount ratio of the sodium nitrate to the concentrated sulfuric acid is 0.5 g:65 mL to 75 mL.
[0025] 2) Slowly adding natural graphite to the sulfuric acid solution of sodium nitrate under ice bath conditions, followed by stirring for 15 min to 25 min to obtain a natural graphite dispersion; wherein the amount ratio of the natural graphite to the concentrated sulfuric acid is 1 g: 65 mL to 75 mL.
[0026] 3) Slowly adding potassium permanganate to the natural graphite dispersion under ice bath conditions, stirring and reacting for 10 h to 14 h to obtain a reaction solution; wherein the mass ratio of the potassium permanganate to the natural graphite is 4.5 to 5.5:1.
[0027] 4) adding water to the reaction solution for dilution under ice bath conditions to obtain a diluted reaction solution; wherein the volume ratio of the dilution water to the reaction solution is 500:65-75.
[0028] 5) After the temperature of the diluted reaction solution drops to room temperature, concentrated hydrochloric acid and water are added in sequence to obtain a reaction treatment solution; wherein the volume ratio of the concentrated hydrochloric acid and water to the concentrated sulfuric acid in step 1) is 10:300:65-75.
[0029] 6) Add hydrogen peroxide solution dropwise to the reaction treatment liquid until the solution turns bright yellow, then stir for 15 to 25 minutes, precipitate until the system separates into layers, and discard the supernatant to obtain the precipitate.
[0030] 7) The precipitated part is repeatedly washed with a large amount of water until the pH of the washing solution is neutral, and then graphene oxide is obtained after drying.
[0031] In the above S2, it should be noted that the present invention first disperses the graphene oxide uniformly in water, and then disperses the modified nano-silicon particles and the reducing agent in the graphene oxide suspension in sequence, so that the modified nano-silicon particles are in full contact with the graphene oxide, so that the modified nano-silicon particles are attached to the surface of the graphene oxide sheet under the action of electrostatic attraction to form graphene oxide loaded with modified nano-silicon particles; at the same time, the reducing agent is uniformly dispersed around the graphene oxide loaded with the modified nano-silicon particles, so as to subsequently reduce the graphene oxide component in the graphene oxide loaded with the modified nano-silicon particles.
[0032] In some preferred embodiments of the present invention, the reducing agent used is any one or more of thiourea, glycine and ascorbic acid, so that the reducing agent used can reduce the graphene oxide component in the graphene oxide loaded with modified nano-silicon particles during subsequent treatment.
[0033] In some more preferred embodiments of the present invention, the reductive agent adopted is thiourea, so that thiourea can not only be used as a reductive agent, thiourea can be decomposed into reducing gases such as ammonia, hydrogen sulfide in a hydrothermal process, thereby participating in reduction reaction by these reducing gases, helping to remove the part of the oxygen-containing functional groups in the graphene oxide, thereby partially recovering its conjugated structure, improving its conductivity. And thiourea also can introduce-NH2,-SO3H functional groups in the reaction process, these functional groups can strengthen the interaction between the graphene sheets, improve the structural stability of composite material. In addition, in the composite process of graphene oxide and nano silicon, thiourea may also play the effect of promoting nano silicon particles to be uniformly dispersed on the graphene oxide surface. This helps to increase the contact area between nano silicon and the graphene oxide, improves the bonding force between the two, thereby obtains a composite material with more excellent performance.
[0034] In some preferred embodiments of the present invention, after adding the modified nano silicon particles and the reducing agent to the graphene oxide suspension, the present invention first performs a stirring treatment and then an ultrasonic treatment to promote uniform dispersion of the modified nano silicon particles and thiourea in the graphene oxide suspension, thereby promoting sufficient contact or reaction between the various components. In some more preferred embodiments of the present invention, the stirring treatment time is 3h to 5h. In some more preferred embodiments of the present invention, the ultrasonic treatment time is 4h to 6h.
[0035] In some preferred embodiments of the present invention, the concentration of the graphene oxide suspension is 1.5 mg / mL to 3 mg / mL to ensure that the graphene oxide in the graphene oxide suspension is uniformly dispersed, thereby facilitating subsequent sufficient contact with the modified nano-silicon particles and thiourea.
[0036] In some preferred embodiments of the present invention, the mass ratio of the modified nano-silicon particles, the reducing agent and the graphene oxide in the graphene oxide suspension is 1:4 to 8:2, so as to ensure that the added modified nano-silicon particles, the reducing agent and the graphene oxide in the graphene oxide suspension can fully react to form aerogel during the hydrothermal reaction.
[0037] In the above S3, it should be noted that, as the hydrothermal reaction proceeds, the temperature and pressure of the reaction system gradually increase, thereby promoting the enhancement of the chemical bond or physical interaction between the nano-silicon particles and the graphene oxide, such as allowing the hydroxyl groups and other active functional groups on the surface of the nano-silicon particles to undergo a dehydration condensation reaction with the carboxyl groups and hydroxyl groups on the carboxyl groups at the edges of the graphene oxide to form a covalent bond. At the same time, as the hydrothermal reaction proceeds, the reducing agent gradually converts the graphene oxide into reduced graphene oxide, and the oxygen-containing functional groups such as hydroxyl groups and carboxyl groups remaining on the surface of the reduced graphene oxide and the hydroxyl groups on the surface of the nano-silicon particles can all serve as donors or acceptors of hydrogen bonds, and are interconnected through hydrogen bonds, making hydrogen bonds an important non-covalent interaction force between the nano-silicon particles and the reduced graphene oxide. When the temperature and pressure of the hydrothermal process are relatively stable, the physical adsorption may be enhanced under the high temperature and high pressure conditions. At the same time, the π electron system of the reduced graphene oxide can undergo π-π stacking with the π electrons on the surface of the nano-silicon particles, so that the above effects act synergistically, and then the graphene oxide gradually forms a graphene aerogel with a three-dimensional structure on the surface of the modified nano-silicon particles during the hydrothermal reaction, thereby forming a graphene aerogel coated with modified nano-silicon particles, providing a porous network structure for the modified nano-silicon particles. The porous network structure can adapt to the volume expansion changes of the modified nano-silicon particles during the electrochemical reaction, thereby effectively alleviating the volume expansion problem of silicon during the charge and discharge process and improving the cycle stability. At the same time, the porous network structure also helps electrolyte transport and can improve the rate capacity of the sodium ion battery. In addition, the continuously interconnected graphene network provides a favorable electron path to counteract the cycle process, thereby improving the conductivity of the overall composite material.
[0038] In some preferred embodiments of the present invention, the temperature of the hydrothermal reaction is 160°C to 180°C, so as to provide a high temperature and high pressure environment for the hydrothermal reaction process, thereby helping to accelerate the rate of the chemical reaction, so that the composite reaction between graphene oxide and nano-silicon can be carried out more fully. In some preferred embodiments of the present invention, the insulation time of the hydrothermal reaction is 12h to 16h to ensure sufficient contact reaction between the reactants, thereby improving the uniformity and quality of the composite material.
[0039] It is understandable that since the composite aerogel matrix after the hydrothermal reaction is present in the reaction liquid, and other impurities may exist in the reaction liquid, it is necessary to take out the formed composite aerogel matrix and wash it to remove the impurities on the surface of the composite aerogel matrix. In some preferred embodiments of the present invention, water and alcohol are used as cleaning agents for washing, and the washing is performed at least 3 times.
[0040] Since there may be residual solvent on the surface of the composite aerogel matrix after the above-mentioned washing treatment, the present invention also performs a drying treatment on the composite aerogel matrix after the washing treatment to remove the interference of the solvent. Among them, in some preferred embodiments of the present invention, the drying treatment is performed by freeze drying to remove the solvent while retaining the original three-dimensional structure of the composite aerogel matrix to obtain a hydrogel precursor. In some more preferred embodiments of the present invention, the vacuum degree of freeze drying is 0MPa to 10MPa, the temperature of freeze drying is -65℃ to -55℃, and the time is 24h to 48h.
[0041] It should be noted that the present invention heat treats the hydrogel precursor to remove residual impurities, improve material structure, enhance interfacial bonding and optimize material properties. In some preferred embodiments of the present invention, the heat treatment is carried out under an inert gas atmosphere to avoid the hydrogel precursor from chemically reacting with other components during the heat treatment, and only the microstructure inside the structure itself will change, such as the rearrangement of carbon atoms, thereby enhancing the degree of graphitization of the material and improving its electrical conductivity, mechanical strength and other properties. Moreover, through heat treatment, the interaction between nano-silicon particles and graphene aerogel can also be promoted to form stronger chemical bonds, such as stronger covalent bonds and hydrogen bonds, thereby enhancing interfacial bonding and improving the stability and durability of the material.
[0042] In some preferred embodiments of the present invention, the heat treatment temperature is 700°C to 800°C, and the holding time is 3h to 5h, so that the microstructure inside the aerogel precursor will be rearranged and reconstructed, thereby optimizing its pore structure and increasing the specific surface area, which is beneficial to improving the performance of the material.
[0043] In some preferred embodiments of the present invention, the heating rate of the heat treatment is 2°C / min to 8°C / min, so as to avoid or reduce the occurrence of material performance degradation or damage due to thermal shock effect caused by too fast a heating rate.
[0044] In some preferred embodiments of the present invention, the inert atmosphere is argon.
[0045] In some preferred embodiments of the present invention, the conductive agent is conductive carbon black; and the binder is polyvinylidene fluoride.
[0046] The present invention also provides a method for preparing the above-mentioned graphene-based nano-silicon composite aerogel negative electrode material, comprising the following steps:
[0047] Step 1: according to the ratio of raw materials for preparing the above-mentioned graphene-based nano-silicon composite aerogel negative electrode material, weigh corresponding masses of graphene / nano-silicon composite aerogel, conductive agent and binder.
[0048] Step 2: Using N-methylpyrrolidone as a ball milling aid, the graphene / nano-silicon composite aerogel, the conductive agent and the binder are mixed and then ball milled to obtain a negative electrode slurry.
[0049] Step 3: coating the negative electrode slurry on the surface of the copper foil and drying it in a vacuum drying oven to obtain the graphene-based nano-silicon composite aerogel negative electrode material.
[0050] It should be noted that, in some preferred embodiments of the present invention, N-methylpyrrolidone is used as a ball milling aid, and the amount of N-methylpyrrolidone used is 2 mL to 3 mL, so as to ensure that the added N-methylpyrrolidone can mix the graphene / nano-silicon composite aerogel, the conductive agent and the binder by ball milling.
[0051] In some preferred embodiments of the present invention, the ball milling speed of the ball milling treatment is 350 r / min to 400 r / min, and the ball milling time is 2 h to 4 h, so as to ensure that the components are fully mixed to obtain a negative electrode slurry with uniform components.
[0052] In some preferred embodiments of the present invention, the coating thickness of the negative electrode slurry when applied on the surface of the copper foil is 10 μm to 20 μm.
[0053] In some preferred embodiments of the present invention, the drying temperature for drying after coating the negative electrode slurry is 110°C to 130°C, and the drying time is 8h to 16h, so that the negative electrode slurry is solidified and a negative electrode coating is formed on the surface of the copper foil, thereby obtaining the graphene-based nano-silicon composite aerogel negative electrode material.
[0054] The present invention also provides an application of the graphene-based nano-silicon composite aerogel negative electrode material as a negative electrode material for a sodium ion battery.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] The present invention uses graphene / nano-silicon composite aerogel as the active material of the negative electrode material of the sodium ion battery, and compounding it with a conductive agent and a binder to form a graphene / nano-silicon composite aerogel negative electrode material for use as the negative electrode material of the sodium ion battery. The graphene / nano-silicon composite aerogel used in the present invention uses a graphene aerogel with a three-dimensional structure as a matrix, and is obtained by uniformly coating and introducing nano-silicon particles inside the graphene aerogel. The porous three-dimensional network structure of the graphene aerogel in the graphene / nano-silicon composite aerogel of the present invention can adapt to the volume expansion change of the modified nano-silicon particles during the electrochemical reaction process, thereby effectively alleviating the volume expansion problem of silicon during the charging and discharging process and improving the cycle stability; moreover, the porous three-dimensional network structure of the graphene aerogel in the graphene / nano-silicon composite aerogel has a porous and high specific surface area structure, which can distribute nano-silicon in the graphene aerogel, effectively avoid the aggregation of nano-silicon, reduce the resistance during the transfer of sodium ions, greatly improve the transmission capacity of sodium ions, and improve the rate capacity of sodium ion batteries, thereby further improving the electrochemical performance of nano-silicon for sodium ion storage. In addition, the continuously interconnected graphene network provides a favorable electron path to resist the cycle process, thereby improving the conductivity of the overall composite material.
[0057] The preparation method of the present invention adopts raw materials from a wide range of sources, the method is simple, easy to operate, can be mass-produced, and is suitable for industrial applications. The graphene-based nano-silicon composite aerogel negative electrode material prepared by the present invention has a high reversible specific capacity, and compared with a pure silicon negative electrode, the cycle stability and capacity are significantly improved.
[0058] The present invention uses nano silicon particles as a matrix, and uses a modifier to modify the nano silicon particles to introduce positive charges on the surface of the nano silicon particles, thereby obtaining modified nano silicon particles with a large amount of positive charges on the surface; then the modified nano silicon particles and a reducing agent are sequentially dispersed in a graphene oxide suspension, so that the modified nano silicon particles are fully in contact with the graphene oxide, so that the modified nano silicon particles are attached to the surface of the graphene oxide sheet under the action of electrostatic attraction, forming graphene oxide loaded with modified nano silicon particles; at the same time, the reducing agent is uniformly dispersed around the graphene oxide loaded with the modified nano silicon particles, so as to subsequently reduce the graphene oxide components in the graphene oxide loaded with the modified nano silicon particles. In the hydrothermal reaction process, the reducing agent can realize the reduction of the graphene oxide components in the graphene oxide loaded with the modified nano silicon particles in the subsequent treatment process; at the same time, the hydroxyl groups and other active functional groups on the surface of the nano silicon particles can undergo a dehydration condensation reaction with the carboxyl groups and hydroxyl groups on the carboxyl groups at the edges of the graphene oxide to form covalent bonds. At the same time, as the hydrothermal reaction proceeds, the reducing agent gradually converts the graphene oxide into reduced graphene oxide, and the oxygen-containing functional groups such as hydroxyl and carboxyl groups remaining on the surface of the reduced graphene oxide and the hydroxyl groups on the surface of the nano-silicon particles can all serve as donors or acceptors of hydrogen bonds, and are interconnected through hydrogen bonds, making hydrogen bonds an important non-covalent interaction force between the nano-silicon particles and the reduced graphene oxide. When the temperature and pressure of the hydrothermal process are relatively stable, the high temperature and high pressure conditions may promote the strengthening of this physical adsorption effect, and at the same time, the π electron system of the reduced graphene oxide can have a π-π stacking effect with the π electrons on the surface of the nano-silicon particles, so that the above effects act synergistically, and then the graphene oxide gradually forms a graphene aerogel with a three-dimensional structure on the surface of the modified nano-silicon particles during the hydrothermal reaction, thereby forming a graphene aerogel material coated with modified nano-silicon particles, and the microstructure inside the aerogel precursor is rearranged and reconstructed after heat treatment, thereby further optimizing the material pore structure, increasing the specific surface area, and further improving the electrochemical properties of the material, and obtaining the graphene / nano-silicon composite aerogel. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 These are scanning electron microscope images of the graphene-based nano-silicon composite aerogel negative electrode material of Example 1, wherein (a) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Example 1 at a 5 μm scale, and (b) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Example 1 at a 1 μm scale.
[0060] Figure 2These are scanning electron microscope images of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 1, wherein (a) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 1 at a 4 μm scale, and (b) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 1 at a 1 μm scale.
[0061] Figure 3 These are scanning electron microscope images of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 2, wherein (a) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 2 at a 5 μm scale, and (b) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 2 at a 30 μm scale.
[0062] Figure 4 It is a scanning electron microscope image of the graphene-based aerogel negative electrode material of Comparative Example 3, wherein (a) and (b) are scanning electron microscope images of different positions of the graphene-based aerogel negative electrode material of Comparative Example 3 at a scale of 50 μm.
[0063] Figure 5 The button-type sodium ion half-cells corresponding to Example 1 and Comparative Examples 1 to 4 are at 0.5A·g -1 Specific capacity plot at current density.
[0064] Figure 6 The figure is a rate diagram of button-type sodium ion half-cells corresponding to Example 1 and Comparative Examples 1 to 4 at different current densities.
[0065] Figure 7 The button-type sodium ion half-cell corresponding to Example 1 at 5A·g -1 Specific capacity diagram at current density.
[0066] Figure 8 The button-type sodium ion half-cell corresponding to Example 1 is 0.2mV·s -1 Cyclic voltammetry curves at scan rate.
[0067] Fig. 9 The button-type sodium ion half-cell corresponding to Comparative Example 1 is 0.2mV·s -1 Cyclic voltammetry curves at scan rate.
[0068] Fig.10 The button-type sodium ion half-cell corresponding to Comparative Example 2 is 0.2mV·s -1 Cyclic voltammetry curves at scan rate.
[0069] Fig.11 The button-type sodium ion half-cell corresponding to Comparative Example 3 is 0.2mV·s-1 Cyclic voltammetry curves at scan rate.
[0070] Fig.12 The button-type sodium ion half-cell corresponding to Comparative Example 4 is 0.2mV·s -1 Cyclic voltammetry curves at scan rate.
[0071] Fig.13 This is the X-ray photoelectron energy spectrum of the graphene-based nano-silicon composite aerogel negative electrode material of Example 1, in which (a) is the full spectrum, (b) is the C1s spectrum, and (c) is the Si2p spectrum. DETAILED DESCRIPTION
[0072] The technical solutions in the embodiments of the present invention are described clearly and completely below. It should be noted that the graphene oxide used in the following embodiments and comparative examples of the present invention is prepared from natural graphite by an improved Hummers method, and is specifically prepared by the following steps:
[0073] 1) In an ice bath, slowly adding sodium nitrate to concentrated sulfuric acid to obtain a sulfuric acid solution of sodium nitrate; wherein the amount ratio of the sodium nitrate to the concentrated sulfuric acid is 0.5 g:70 mL.
[0074] 2) Slowly adding natural graphite to the sulfuric acid solution of sodium nitrate under ice bath conditions, followed by stirring for 20 minutes to obtain a natural graphite dispersion; wherein the amount ratio of the natural graphite to the concentrated sulfuric acid is 1 g:70 mL.
[0075] 3) Continue to slowly add potassium permanganate to the above natural graphite dispersion under ice bath conditions, stir and react for 12 hours to obtain a reaction solution; wherein the mass ratio of the potassium permanganate to the natural graphite is 5:1.
[0076] 4) adding water to the reaction solution for dilution under ice bath conditions to obtain a diluted reaction solution; wherein the volume ratio of the dilution water to the reaction solution is 500:70.
[0077] 5) After the temperature of the diluted reaction solution drops to room temperature, concentrated hydrochloric acid and water are added in sequence to obtain a reaction treatment solution; wherein the volume ratio of the concentrated hydrochloric acid and water to the concentrated sulfuric acid in step 1) is 10:300:70.
[0078] 6) Add hydrogen peroxide solution dropwise to the reaction treatment liquid until the solution turns bright yellow, then stir for 20 minutes, precipitate until the system separates into layers, and discard the supernatant to obtain the precipitate.
[0079] 7) The precipitated part is repeatedly washed with a large amount of water until the pH of the washing solution is neutral, and then graphene oxide is obtained after drying.
[0080] Example 1
[0081] This embodiment provides a graphene-based nano-silicon composite aerogel negative electrode material, and the raw materials for preparing the negative electrode material include 80% of graphene / nano-silicon composite aerogel, 10% of conductive agent and 10% of binder in terms of mass percentage.
[0082] In this embodiment, the graphene-based nano-silicon composite aerogel negative electrode material is prepared by the following steps:
[0083] Step 1, preparation of graphene / nano-silicon composite aerogel:
[0084] 1.1) In this embodiment, PDDA is used as a modifier, 3 g of PDDA is dispersed in 60 mL of deionized water, and then 120 mg of nano silicon particles are added, and then ultrasonic treatment is performed for 2 hours, and then stirring treatment is performed for 12 hours. Then the solution system after stirring treatment is repeatedly centrifuged and washed 4 times, and the centrifugal speed during each centrifugal washing treatment is 9000 rpm, and the time is 5 minutes to 10 minutes to ensure that the solute is completely centrifuged out, and the supernatant and the solute are clearly defined to wash away the excess PDDA, and then the washed product is vacuum dried at 110°C for 36 hours to obtain modified nano silicon particles.
[0085] 1.2) According to the mass ratio of modified nano silicon particles, graphene oxide and thiourea of 1:2:4, the corresponding masses of modified nano silicon particles, graphene oxide and thiourea are weighed and set aside. The weighed graphene oxide is dispersed in water to form a graphene oxide suspension with a concentration of 2 mg / mL. The weighed modified nano silicon particles and thiourea are then dispersed in the graphene oxide suspension in sequence, followed by stirring for 4 hours, and then ultrasonically treated for 5 hours to obtain a mixed solution.
[0086] 1.3) The mixed solution obtained in 1.2) was transferred to a polytetrafluoroethylene-lined autoclave, sealed, and kept at a hydrothermal reaction temperature of 180°C for 12 hours. After the heat preservation, it was naturally cooled to room temperature to form a black columnar hydrogel in the autoclave. After the black columnar hydrogel was taken out, it was repeatedly washed with deionized water and alcohol alternately, and then dried in freeze drying for 48 hours to obtain a hydrogel precursor.
[0087] 1.4) The hydrogel precursor was placed in a quartz tube furnace, heated to 800°C at a heating rate of 5°C / min under an argon atmosphere, and kept at 800°C for 3 h to obtain a graphene / nano-silicon composite aerogel.
[0088] Step 2: In this embodiment, acetylene black is used as a conductive agent and PVDF is used as a binder. According to the above ratio, 8 g of graphene / nano-silicon composite aerogel, 1 g of acetylene black and 1 g of PVDF are weighed and set aside.
[0089] Step 3: Using N-methylpyrrolidone as a ball milling aid, 2 mL to 3 mL of N-methylpyrrolidone is mixed with the above-mentioned graphene / nano-silicon composite aerogel, acetylene black and PVDF, and then ball milled for 3 hours to obtain a negative electrode slurry.
[0090] Step 4, coating the negative electrode slurry obtained in the above step 3 on the surface of the copper foil with a coating thickness of 15 μm, placing it in a vacuum drying oven at 120° C. and drying it for 12 hours to obtain the graphene-based nano-silicon composite aerogel negative electrode material.
[0091] The graphene-based nano-silicon composite aerogel negative electrode material of this embodiment is recorded as PDDA@Si@RGA.
[0092] Example 2
[0093] The present embodiment provides a graphene-based nano-silicon composite aerogel negative electrode material, and the raw materials for preparing the negative electrode material include, by weight percentage, 76% of graphene / nano-silicon composite aerogel, 12% of conductive agent, and 12% of binder.
[0094] And it is prepared by the following steps:
[0095] Step 1, preparation of graphene / nano-silicon composite aerogel:
[0096] 1.1) In this embodiment, PDDA is used as a modifier, 2.4 g of PDDA is dispersed in 50 mL of deionized water, and then 120 mg of nano silicon particles are added, and then ultrasonic treatment is performed for 1 hour, and then stirring treatment is performed for 6 hours. Then the solution system after stirring treatment is repeatedly centrifuged and washed 4 times, and the centrifugal speed during each centrifugal washing treatment is 8000 rpm, and the time is 5 minutes to 10 minutes, so as to ensure that the solute is completely centrifuged out, and the supernatant and the solute are clearly defined to wash away the excess PDDA, and then the washed product is vacuum dried at 100°C for 30 hours to obtain modified nano silicon particles.
[0097] 1.2) According to the mass ratio of modified nano silicon particles, graphene oxide and thiourea of 1:2:6, the corresponding mass of modified nano silicon particles, graphene oxide and thiourea are weighed and set aside. The weighed graphene oxide is dispersed in water to form a graphene oxide suspension with a concentration of 1.5 mg / mL. The weighed modified nano silicon particles and thiourea are then dispersed in the graphene oxide suspension in sequence, followed by stirring for 3 hours, and then ultrasonically treated for 4 hours to obtain a mixed solution.
[0098] 1.3) The mixed solution obtained in 1.2) was transferred to a polytetrafluoroethylene-lined autoclave, sealed, and kept at a hydrothermal reaction temperature of 160°C for 14 hours. After the heat preservation, it was naturally cooled to room temperature to form a black columnar hydrogel in the autoclave. After the black columnar hydrogel was taken out, it was repeatedly washed with deionized water and alcohol alternately, and then dried in a freeze-drying process at -65°C for 24 hours to obtain a hydrogel precursor.
[0099] 1.4) The hydrogel precursor was placed in a quartz tube furnace, heated to 700°C at a heating rate of 2°C / min under an argon atmosphere, and kept at 700°C for 4 h to obtain a graphene / nano-silicon composite aerogel.
[0100] Step 2: In this embodiment, acetylene black is used as a conductive agent and PVDF is used as a binder. According to the above ratio, 7.6 g of graphene / nano-silicon composite aerogel, 1.2 g of acetylene black and 1.2 g of PVDF are weighed and set aside.
[0101] Step 3: Using N-methylpyrrolidone as a ball milling aid, 2 mL to 3 mL of N-methylpyrrolidone is mixed with the above-mentioned graphene / nano-silicon composite aerogel, acetylene black and PVDF, and then ball milled for 3 hours to obtain a negative electrode slurry.
[0102] Step 4, coating the negative electrode slurry obtained in the above step 3 on the surface of the copper foil with a coating thickness of 10 μm, placing it in a vacuum drying oven at 110° C. and drying it for 16 hours to obtain the graphene-based nano-silicon composite aerogel negative electrode material.
[0103] Example 3
[0104] This embodiment provides a graphene-based nano-silicon composite aerogel negative electrode material, and the raw materials for preparing the negative electrode material include 84% of graphene / nano-silicon composite aerogel, 8% of conductive agent and 8% of binder in terms of mass percentage.
[0105] Please also see Figure 1 In this embodiment, the graphene-based nano-silicon composite aerogel negative electrode material is prepared by the following steps:
[0106] Step 1, preparation of graphene / nano-silicon composite aerogel:
[0107] 1.1) In this embodiment, PDDA is used as a modifier, 3.6 g of PDDA is dispersed in 100 mL of deionized water, and then 120 mg of nano silicon particles are added, and then ultrasonic treatment is performed for 3 hours, and then stirring treatment is performed for 18 hours. Then the solution system after stirring treatment is repeatedly centrifuged and washed 4 times, and the centrifugal speed during each centrifugal washing treatment is 10000 rpm, and the time is 5 minutes to 10 minutes to ensure that the solute is completely centrifuged out, and the supernatant and the solute are clearly defined to wash away the excess PDDA, and then the washed product is vacuum dried at 120°C for 36 hours to obtain modified nano silicon particles.
[0108] 1.2) According to the mass ratio of modified nano silicon particles, graphene oxide and thiourea of 1:2:8, the corresponding mass of modified nano silicon particles, graphene oxide and thiourea are weighed and set aside. The weighed graphene oxide is dispersed in water to form a graphene oxide suspension with a concentration of 3 mg / mL. The weighed modified nano silicon particles and thiourea are then dispersed in the graphene oxide suspension in sequence, followed by stirring for 5 hours, and then ultrasonically treated for 6 hours to obtain a mixed solution.
[0109] 1.3) The mixed solution obtained in 1.2) was transferred to a polytetrafluoroethylene-lined autoclave, sealed, and kept at a hydrothermal reaction temperature of 170°C for 16 hours. After the heat preservation, it was naturally cooled to room temperature to form a black columnar hydrogel in the autoclave. After the black columnar hydrogel was taken out, it was repeatedly washed with deionized water and alcohol alternately, and then dried in a freeze-drying process at -55°C for 24 hours to obtain a hydrogel precursor.
[0110] 1.4) The hydrogel precursor was placed in a quartz tube furnace, heated to 750°C at a heating rate of 8°C / min under an argon atmosphere, and kept at 750°C for 5 h to obtain a graphene / nano-silicon composite aerogel.
[0111] Step 2: In this embodiment, acetylene black is used as a conductive agent and PVDF is used as a binder. According to the above ratio, 8.4 g of graphene / nano-silicon composite aerogel, 0.8 g of acetylene black and 0.8 g of PVDF are weighed and set aside.
[0112] Step 3: Using N-methylpyrrolidone as a ball milling aid, 2 mL to 3 mL of N-methylpyrrolidone is mixed with the above-mentioned graphene / nano-silicon composite aerogel, acetylene black and PVDF, and then ball milled for 3 hours to obtain a negative electrode slurry.
[0113] Step 4, coating the negative electrode slurry obtained in the above step 3 on the surface of the copper foil with a coating thickness of 20 μm, placing it in a vacuum drying oven at 130° C. for h to obtain the graphene-based nano-silicon composite aerogel negative electrode material.
[0114] Comparative Example 1
[0115] This embodiment provides a graphene-based nano-silicon composite aerogel negative electrode material, and the raw materials for preparing the negative electrode material include 80% of graphene / nano-silicon composite aerogel, 10% of conductive agent and 10% of binder in terms of mass percentage.
[0116] In this embodiment, the graphene-based nano-silicon composite aerogel negative electrode material is prepared by the following steps:
[0117] Step 1, preparation of graphene / nano-silicon composite aerogel:
[0118] 1.1) In this example, PDDA was used as a modifier, 3 g of PDDA was dispersed in 60 mL of deionized water, and then 120 mg of nano silicon particles were added, and then ultrasonic treatment was performed for 2 h, and then stirred for 12 h. The solution system after stirring was then repeatedly centrifuged for 4 times, and the centrifugal speed during each centrifugal washing treatment was 9000 rpm, and the time was 5 min to 10 min to wash away excess PDDA, and then the washed product was vacuum dried at 110 ° C for 36 h to obtain modified nano silicon particles.
[0119] 1.2) According to the mass ratio of modified nano silicon particles, graphene oxide and thiourea of 1:1:2, corresponding masses of modified nano silicon particles, graphene oxide and thiourea are weighed and set aside. The weighed graphene oxide is dispersed in water to form a graphene oxide suspension with a concentration of 2 mg / mL. The weighed modified nano silicon particles and thiourea are then dispersed in the graphene oxide suspension in sequence, followed by stirring for 4 hours, and then ultrasonically treated for 5 hours to obtain a mixed solution.
[0120] 1.3) The mixed solution obtained in 1.2) was transferred to a polytetrafluoroethylene-lined autoclave, sealed, and kept at a hydrothermal reaction temperature of 180°C for 12 hours. After the heat preservation, it was naturally cooled to room temperature to form a black columnar hydrogel in the autoclave. After the black columnar hydrogel was taken out, it was repeatedly washed with deionized water and alcohol alternately, and then dried in freeze drying for 48 hours to obtain a hydrogel precursor.
[0121] 1.4) The hydrogel precursor was placed in a quartz tube furnace, heated to 800°C at a heating rate of 5°C / min under an argon atmosphere, and kept at 800°C for 3 h to obtain a graphene / nano-silicon composite aerogel.
[0122] Step 2: In this embodiment, acetylene black is used as a conductive agent and PVDF is used as a binder. According to the above ratio, 8 g of graphene / nano-silicon composite aerogel, 1 g of acetylene black and 1 g of PVDF are weighed and set aside.
[0123] Step 3: Using N-methylpyrrolidone as a ball milling aid, 2 mL to 3 mL of N-methylpyrrolidone is mixed with the above-mentioned graphene / nano-silicon composite aerogel, acetylene black and PVDF, and then ball milled for 3 hours to obtain a negative electrode slurry.
[0124] Step 4, coating the negative electrode slurry obtained in the above step 3 on the surface of the copper foil with a coating thickness of 15 μm, placing it in a vacuum drying oven at 120° C. and drying it for 12 hours to obtain the graphene-based nano-silicon composite aerogel negative electrode material.
[0125] That is, the difference between this embodiment and embodiment 1 is only that:
[0126] In the present embodiment, when preparing the graphene / nano-silicon composite aerogel, the mass ratio of the modified nano-silicon particles, graphene oxide and thiourea is 1:1:2.
[0127] The graphene-based nano-silicon composite aerogel negative electrode material of this embodiment is recorded as 2PDDA@Si@RGA.
[0128] Comparative Example 2
[0129] This comparative example provides a graphene-based nano-silicon composite aerogel negative electrode material, and its preparation raw materials, calculated by mass percentage, include 80% of graphene / nano-silicon composite aerogel, 10% of conductive agent and 10% of binder.
[0130] In this comparative example, the graphene-based nano-silicon composite aerogel negative electrode material is prepared by the following steps:
[0131] Step 1, preparation of graphene / nano-silicon composite aerogel:
[0132] 1.1) According to the mass ratio of nano-silicon particles, graphene oxide and thiourea of 1:2:4, weigh the corresponding mass of nano-silicon particles, graphene oxide and thiourea respectively for use. Disperse the weighed graphene oxide in water to form a graphene oxide suspension with a concentration of 2 mg / mL. Then, 120 mg of the weighed nano-silicon particles and thiourea are dispersed in the graphene oxide suspension in sequence, followed by stirring for 4 h, and then ultrasonically treating for 5 h to obtain a mixed solution.
[0133] 1.2) The obtained mixed solution was transferred to a polytetrafluoroethylene-lined autoclave, sealed, and kept at a hydrothermal reaction temperature of 180°C for 12 hours. After the heat preservation, it was naturally cooled to room temperature to form a black columnar hydrogel in the autoclave. After the black columnar hydrogel was taken out, it was repeatedly washed with deionized water and alcohol alternately, and then dried in freeze drying for 48 hours to obtain a hydrogel precursor.
[0134] 1.3) The hydrogel precursor was placed in a quartz tube furnace, heated to 800°C at a heating rate of 5°C / min under an argon atmosphere, and kept at 800°C for 3 h to obtain a graphene / nano-silicon composite aerogel.
[0135] Step 2: In this comparative example, acetylene black is used as a conductive agent and PVDF is used as a binder. According to the above ratio, 8 g of graphene / nano-silicon composite aerogel, 1 g of acetylene black and 1 g of PVDF are weighed and set aside.
[0136] Step 3: Using N-methylpyrrolidone as a ball milling aid, 2 mL to 3 mL of N-methylpyrrolidone is mixed with the above-mentioned graphene / nano-silicon composite aerogel, acetylene black and PVDF, and then ball milled for 3 hours to obtain a negative electrode slurry.
[0137] Step 4, coating the negative electrode slurry obtained in the above step 3 on the surface of the copper foil with a coating thickness of 15 μm, placing it in a vacuum drying oven at 120° C. and drying it for 12 hours to obtain the graphene-based nano-silicon composite aerogel negative electrode material.
[0138] That is, the difference between this comparative example and Example 1 is only that:
[0139] In this comparative example, no modification treatment is performed on the nano-silicon.
[0140] The graphene-based nano-silicon composite aerogel negative electrode material of this comparative example is recorded as Si@RGA.
[0141] Comparative Example 3
[0142] This comparative example provides a graphene-based aerogel negative electrode material, and the raw materials for preparing the anode material include 80% of graphene aerogel, 10% of conductive agent and 10% of binder in terms of mass percentage.
[0143] In this comparative example, the graphene-based aerogel negative electrode material is prepared by the following steps:
[0144] Step 1, preparation of graphene aerogel:
[0145] 1.1) Graphene oxide is dispersed in water to form a graphene oxide suspension with a concentration of 2 mg / mL, followed by stirring for 4 h and ultrasonic treatment for 5 h to obtain a mixed solution.
[0146] 1.2) The mixed solution obtained in 1.1) was transferred to a polytetrafluoroethylene-lined autoclave, sealed, and kept at a hydrothermal reaction temperature of 180°C for 12 hours. After the heat preservation, it was naturally cooled to room temperature to form a black columnar hydrogel in the autoclave. After the black columnar hydrogel was taken out, it was repeatedly washed with deionized water and alcohol alternately, and then dried in freeze drying for 48 hours to obtain a hydrogel precursor.
[0147] 1.3) The hydrogel precursor was placed in a quartz tube furnace, heated to 800°C at a heating rate of 5°C / min under an argon atmosphere, and kept at 800°C for 3 h to obtain graphene aerogel.
[0148] Step 2: In this comparative example, acetylene black is used as a conductive agent and PVDF is used as a binder. According to the above ratio, 8 g of graphene aerogel, 1 g of acetylene black and 1 g of PVDF are weighed and set aside.
[0149] Step 3: Using N-methylpyrrolidone as a ball milling aid, 2 mL to 3 mL of N-methylpyrrolidone is mixed with the above-weighed graphene aerogel, acetylene black and PVDF, and then ball milled for 3 hours to obtain a negative electrode slurry.
[0150] Step 4, coating the negative electrode slurry obtained in the above step 3 on the surface of the copper foil with a coating thickness of 15 μm, placing it in a vacuum drying oven at 120° C. and drying it for 12 hours to obtain the graphene-based aerogel negative electrode material.
[0151] That is, the difference between this comparative example and Example 1 is only that:
[0152] This comparative example does not introduce modified nano-silicon particles.
[0153] The graphene-based aerogel negative electrode material of this comparative example is recorded as GA.
[0154] Comparative Example 4
[0155] This comparative example provides a nano-silicon negative electrode material, and the raw materials for preparing the nano-silicon negative electrode material include 80% nano-silicon, 10% conductive agent and 10% binder in terms of mass percentage.
[0156] In this comparative example, the nano silicon negative electrode material is prepared by the following steps:
[0157] Step 1: In this comparative example, acetylene black is used as a conductive agent and PVDF is used as a binder. According to the above ratio, 8 g of nano-silicon, 1 g of acetylene black and 1 g of PVDF are weighed and set aside.
[0158] Step 2: Using N-methylpyrrolidone as a ball milling aid, take 2 mL to 3 mL of N-methylpyrrolidone and mix it with the weighed nano-silicon, acetylene black and PVDF, and then ball mill it for 3 hours to obtain a negative electrode slurry.
[0159] Step 4: coating the negative electrode slurry obtained in the above step 3 on the surface of the copper foil with a coating thickness of 15 μm, and drying it in a vacuum drying oven at 120° C. for 12 hours to obtain the nano-silicon negative electrode material.
[0160] The graphene-based nano-silicon composite aerogel negative electrode material of this comparative example is denoted as Si.
[0161] Experimental Section
[0162] (I) Microscopic morphology test
[0163] The present invention found during testing that the morphology of the negative electrode materials prepared in Example 2 and Example 3 has a microscopic morphology highly similar to that of Example 1. Therefore, the present invention mainly takes the negative electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 as examples, and performs scanning electron microscope tests on them. The test results are as follows: Figure 1 to Figure 4 shown.
[0164] Figure 1 These are scanning electron microscope images of the graphene-based nano-silicon composite aerogel negative electrode material of Example 1, wherein (a) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Example 1 at a 5 μm scale, and (b) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Example 1 at a 1 μm scale.
[0165] And by Figure 1 It can be seen from the test results that the nano-silicon modified by PDDA is evenly loaded on the graphene sheet without obvious aggregation or agglomeration, which shows that the preparation method of the present invention can successfully and stably combine the nano-silicon with the graphene sheet.
[0166] Figure 2 These are scanning electron microscope images of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 1, wherein (a) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 1 at a 4 μm scale, and (b) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 1 at a 1 μm scale.
[0167] By comparison Figure 2 and Figure 1 It can be seen from the test results that, since the amount of graphene oxide added in Comparative Example 1 is reduced compared with that in Example 1, that is, the amount of modified nano-silicon particles added in Comparative Example 1 is excessive relative to the amount of graphene oxide, the relative loading amount of the modified nano-silicon particles on the graphene sheets increases, causing the modified nano-silicon particles to aggregate on the graphene sheets.
[0168] Figure 3 These are scanning electron microscope images of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 2, wherein (a) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 2 at a 5 μm scale, and (b) is a scanning electron microscope image of the graphene-based nano-silicon composite aerogel negative electrode material of Comparative Example 2 at a 30 μm scale.
[0169] By comparison Figure 3 and Figure 1 The test results show that the composite effect of nano-silicon without PDDA modification and graphene oxide is very poor, the dispersion on the graphene sheet is poor, a large amount of nano-silicon agglomerates on the graphene surface, resulting in uneven distribution of nano-silicon particles on the graphene surface, making it difficult to effectively realize the composite of nano-silicon particles on graphene.
[0170] Figure 4 It is a scanning electron microscope image of the graphene-based aerogel negative electrode material of Comparative Example 3, wherein (a) and (b) are scanning electron microscope images of different positions of the graphene-based aerogel negative electrode material of Comparative Example 3 at a scale of 50 μm.
[0171] And by Figure 4 From the test results, it can be seen that the layered structure of pure graphene aerogel can be clearly observed through SEM images. This layered structure is composed of stacked graphene sheets to form a porous three-dimensional network. In addition, surface roughness, wrinkles and folds can also be observed. These features not only increase the specific surface area of the aerogel, but also provide it with more adsorption sites and reactive sites.
[0172] (II) Electrochemical performance test
[0173] The present invention takes the negative electrode materials of Example 1 and Comparative Examples 1 to 4 as examples, and makes them into electrode sheets with a diameter of 12 mm respectively, and puts the electrode sheets corresponding to Example 1 and Comparative Examples 1 to 4 into a glove box filled with argon atmosphere, and assembles the electrode sheets, diaphragms and sodium sheets into button-type sodium ion half-cells by conventional methods.
[0174] The button-type sodium ion half cells corresponding to Example 1 and Comparative Examples 1 to 4 were respectively tested at 0.5 A·g -1 The cycle performance test was carried out under the current density, and the test results are as follows Figure 5 to Figure 7 shown.
[0175] Figure 5 The button-type sodium ion half-cells corresponding to Example 1 and Comparative Examples 1 to 4 are at 0.5A·g -1 The specific capacity diagram under current density shows that the button-type sodium ion half-cell corresponding to Example 1 has a current density of 0.5A·g -1 The first cycle discharge capacity at the current density is as high as 340.2 mAh g -1 After 100 cycles, the reversible specific capacity still remains at 217.4 mAh g -1 The button-type sodium ion half-cell corresponding to Comparative Example 1 is at 0.5A·g -1The first cycle discharge capacity at the current density is only 183.9 mAh g -1 After 100 cycles, the reversible specific capacity is 74.2 mAh g -1 The button-type sodium ion half-cell corresponding to Comparative Example 2 is 0.5A·g -1 The first cycle discharge capacity at current density is 207.5 mAh g -1 After 100 cycles, the reversible specific capacity is 108.4 mAh g -1 The button-type sodium ion half-cell corresponding to Comparative Example 3 is 0.5A·g -1 The first cycle discharge capacity at current density is 150 mAh g -1 After 100 cycles, the reversible specific capacity is 126 mAh g -1 The button-type sodium ion half-cell corresponding to Comparative Example 4 is 0.5A·g -1 The first cycle discharge capacity at the current density is only 36.2 mAh g -1 After 100 cycles, the reversible specific capacity is 5.7 mAh g -1 By comparing the test results of Example 1 and Comparative Examples 1 to Comparative Examples 4, it can be seen that Example 1 has the highest charge-discharge specific capacity during 100 cycles and the best cycle stability.
[0176] Figure 6 The rate diagrams of button-type sodium ion half-cells corresponding to Example 1 and Comparative Examples 1 to 4 at different current densities are shown, wherein the different current densities include 0.1 A·g -1 , 0.2A·g -1 , 0.5A·g -1 , 1A·g -1 , 2A·g -1 , 5A g -1 and 0.1A·g -1 . And by Figure 6 It can be seen that the rate performance of Example 1 at different current densities is the best, and when the current returns to 0.1 A·g -1 The charge-discharge specific capacity also quickly recovered to normal values. The button-type sodium ion half-cells corresponding to Comparative Examples 1 to 4 have poor rate performance at different current densities, which may be due to the difficulty in achieving the composite of nano-silicon and graphene aerogel. This also shows that the composite of graphene in the form of graphene aerogel with a three-dimensional structure and nano-silicon to form a composite aerogel structure with a three-dimensional structure has an important influence on effectively improving the electrochemical performance of nano-silicon for sodium ion storage.
[0177] The present invention also conducts electrochemical performance tests on button-type sodium ion half-cells corresponding to Example 2 and Example 3, and the test results show that the button-type sodium ion half-cells corresponding to Example 2 and Example 3 have an electrochemical performance of 0.5A·g -1 The first cycle discharge specific capacity under the current density is 97% to 99% of that in Example 1, and the reversible specific capacity after 100 cycles is 95% to 98% of that in Example 1.
[0178] Figure 7 The button-type sodium ion half-cell corresponding to Example 1 at 5A·g -1 The specific capacity diagram at the current density of . And by Figure 7 It can be seen that Example 1 has outstanding performance in high current long cycle. -1 The battery can be cycled stably for 1000 times without capacity attenuation at a current density of .
[0179] The present invention also tests the button-type sodium ion half-cells corresponding to Example 1 and Comparative Examples 1 to 4 at 0.2 mV·s -1 Cyclic voltammetry was performed at a scan rate of Figure 8 to Figure 12 shown.
[0180] Figure 8 The button-type sodium ion half-cell corresponding to Example 1 is 0.2mV·s -1 From the cyclic voltammetry curve at the scanning rate, it can be seen that in the first cycle, at a voltage below 0.1V, crystalline silicon reacts with sodium to form amorphous NaxSi. There is a wide reduction peak at around 1.9V, which is due to the formation of the solid-electrolyte interphase SEI on the composite material and the reaction of sodium ions with residual graphene oxide oxygen-containing groups. In the subsequent cycles, two oxidation peaks at 0.57 and 0.83V were observed, corresponding to the decay and sodiumization of amorphous Si, respectively. In addition, the positions of the oxidation peak and the reduction peak no longer change, and the CV curve overlap is high, indicating that the charge and discharge reaction of Example 1 has high reversibility.
[0181] Fig. 9 The button-type sodium ion half-cell corresponding to Comparative Example 1 is 0.2mV·s -1 From the cyclic voltammetry curves at the scanning rate, it can be seen that the CV curve of the first cycle is roughly consistent with that of Example 1. The position of the oxidation peak has not changed much, at 0.56V and 0.83V respectively. The reduction peak is increased to about 2V compared with Example 1, and the reduction peak moves toward the high potential direction, which means that the polarization phenomenon is weakened. However, compared with the subsequent CV curves, the reversibility is poor, and the side reactions produced are also obvious, which is the main reason for its low capacity.
[0182] Fig.10 The button-type sodium ion half-cell corresponding to Comparative Example 2 is 0.2mV·s-1 From the cyclic voltammetry curves at the scanning rate, it can be seen that it is almost difficult to determine the effective discharge platform during the first scan, which means that it is difficult to form an effective contact when nano-silicon is directly composited with graphene oxide without surface modification. The formation of the solid electrolyte interface (SEI) film and the irreversible insertion of Na ions into Si particles are almost impossible. In the subsequent scans, the broad reduction peak at 2.0 disappears. The reason for this phenomenon is most likely the agglomeration of nano-silicon, which affects the electrochemical active area of the electrode material and the transmission path of sodium ions, resulting in changes in the reduction peak.
[0183] Fig.11 The button-type sodium ion half-cell corresponding to Comparative Example 3 is 0.2mV·s -1 From the cyclic voltammetry curves at the scanning rate, it can be seen that the typical CV scanning curve of graphene aerogel in sodium ion battery, the peak shape on the CV curve of graphene aerogel is usually smoother, indicating that its electrochemical reaction process is relatively uniform. This shows that during the charge and discharge process, sodium ions can be easily embedded and removed from the graphene aerogel, and this process has high reversibility. After multiple CV scans, the shape and peak position of the CV curve of the graphene aerogel can usually remain stable, indicating that it has good electrochemical stability.
[0184] Fig.12 The button-type sodium ion half-cell corresponding to Comparative Example 4 is 0.2mV·s -1 From the cyclic voltammetry curves under the scanning rate, it can be seen that the CV scanning curve of the pure silicon negative electrode material is different after each CV scanning, which indicates that the electrochemical stability of silicon as a negative electrode material for sodium ion batteries is extremely poor, and it is difficult to use it as a negative electrode material for sodium ion batteries.
[0185] Based on the above test results, it can be seen that the electrochemical performance of the negative electrode material of Example 1 is better than that of the negative electrode materials of Comparative Examples 1-4, which shows that constructing a graphene aerogel coated with modified nano-silicon particles is very important for improving the electrochemical performance of nano-silicon materials as negative electrode materials for sodium ion batteries. The graphene aerogel coated with modified nano-silicon particles can provide a porous network structure for the modified nano-silicon particles, and the porous network structure can adapt to the volume expansion changes of the modified nano-silicon particles during the electrochemical reaction process, thereby effectively alleviating the volume expansion problem of silicon during the charge and discharge process and improving the cycle stability. At the same time, the porous network structure also helps electrolyte transport and can improve the rate capacity of the sodium ion battery. In addition, the continuously interconnected graphene network provides a favorable electron path to counteract the cycle process, thereby improving the conductivity of the overall composite material.
[0186] (III) X-ray photoelectron spectroscopy test
[0187] The present invention also performs an X-ray photoelectron spectroscopy test on the graphene-based nano-silicon composite aerogel negative electrode material of Example 1, and the test results are as follows: Fig.13 shown.
[0188] Fig.13 This is the X-ray photoelectron energy spectrum of the graphene-based nano-silicon composite aerogel negative electrode material of Example 1, in which (a) is the full spectrum, (b) is the C1s spectrum, and (c) is the Si2p spectrum.
[0189] Depend on Fig.13 In Figure (a), we can observe the obvious coexistence of C, O, and Si elements. Fig.13 As can be seen from Figures (b) and (c), the CC bond is a standard 284.8 eV, and Si-C is 284.6 eV. The existence of the Si-C bond indicates that during the preparation of the graphene aerogel and nano-silicon composite material, a chemical reaction occurred between the carbon atoms of graphene and the silicon atoms of nano-silicon to form a covalent bond. In addition, the formation of the Si-C bond enhances the interfacial bonding strength between graphene and nano-silicon, which provides a basis for the subsequent improvement of electrochemical performance. The C-OH bond is 285.6 eV. The introduction of the C-OH bond can improve the stability of the composite material, such as by forming hydrogen bonds and other interactions to enhance the internal bonding of the material.
[0190] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A graphene-based nano-silicon composite aerogel negative electrode material, wherein the graphene-based nano-silicon composite aerogel negative electrode material is used for a sodium ion battery, characterized in that: The raw materials for its preparation include, by weight percentage: Graphene / nano-silicon composite aerogel 75% to 85%, conductive agent 8% to 12% and binder 8% to 12%, totaling 100%; The graphene / nano-silicon composite aerogel is based on a graphene aerogel with a three-dimensional structure and is obtained by uniformly coating and introducing nano-silicon particles inside the graphene aerogel.
2. The graphene-based nano-silicon composite aerogel negative electrode material according to claim 1, characterized in that: The graphene / nano-silicon composite aerogel is prepared by the following steps: In water, modifying the nano silicon particles by using a modifier to introduce positive charges on the surface of the nano silicon particles to obtain modified nano silicon particles; The graphene oxide is uniformly dispersed in water to form a graphene oxide suspension; the modified nano-silicon particles and the reducing agent are sequentially dispersed in the graphene oxide suspension and mixed to obtain a mixed solution; The mixed solution is subjected to a hydrothermal reaction, washed and freeze-dried to obtain a hydrogel precursor; The hydrogel precursor is subjected to heat treatment in an inert atmosphere to obtain the graphene / nano-silicon composite aerogel.
3. The graphene-based nano-silicon composite aerogel negative electrode material according to claim 2, characterized in that: The modifier is any one of polydiallyldimethylammonium chloride, polyacrylamide and polyaniline.
4. The graphene-based nano-silicon composite aerogel negative electrode material according to claim 2, characterized in that: The mass ratio of the modifier to the nano silicon particles is 20 to 30:
1.
5. The graphene-based nano-silicon composite aerogel negative electrode material according to claim 2, characterized in that: The mass ratio of the modified nano silicon particles, the reducing agent and the graphene oxide in the graphene oxide suspension is 1:4 to 8:
2.
6. The graphene-based nano-silicon composite aerogel negative electrode material according to claim 2, characterized in that: The reducing agent is any one or more of thiourea, glycine and ascorbic acid.
7. The graphene-based nano-silicon composite aerogel negative electrode material according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 160°C to 180°C, and the insulation time is 12h to 16h; The heat treatment temperature is 700° C. to 800° C., and the heat preservation time is 3 h to 5 h.
8. The graphene-based nano-silicon composite aerogel negative electrode material according to claim 1, characterized in that: The conductive agent is conductive carbon black; the binder is polyvinylidene fluoride.
9. A method for preparing the graphene-based nano-silicon composite aerogel negative electrode material according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the ratio of the raw materials for preparing the graphene-based nano-silicon composite aerogel negative electrode material according to any one of claims 1 to 8, weigh the corresponding mass of graphene / nano-silicon composite aerogel, conductive agent and binder; Using N-methylpyrrolidone as a ball milling aid, the graphene / nano-silicon composite aerogel, a conductive agent and a binder are mixed and then ball milled to obtain a negative electrode slurry; The negative electrode slurry is coated on the surface of the copper foil and placed in a vacuum drying oven for drying to obtain the graphene-based nano-silicon composite aerogel negative electrode material.
10. Use of the graphene-based nano-silicon composite aerogel negative electrode material according to any one of claims 1 to 8 in a sodium ion battery.
Citation Information
Patent Citations
Graphene scroll-encapsulated nanometer silicon particle composite electrode material and preparing method thereof
CN105883716A
Preparation method of flexible self-supporting silicon / graphene cathode material of lithium ion battery
CN109524641A
Preparation method of micron silicon-graphene composite aerogel, electrode and preparation method thereof
CN115282891A
Sodium-ion battery graphene-like ultrathin nanometer negative electrode material, and preparation method and application thereof
CN117936756A
Sealing washer for a rotor, and rotor with such a washer
KR1020210119316A
Cited By
Graphene composite lithium ion battery negative electrode material and preparation method thereof
CN120767312A
